2003
DOI: 10.1046/j.1464-5491.2003.00895.x
|View full text |Cite
|
Sign up to set email alerts
|

Cause‐specific and total mortality in the Canterbury (New Zealand) insulin‐treated Diabetic Registry population: a 15‐year follow‐up study

Abstract: Mortality rates are high for insulin-treated diabetic individuals relative to the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
2
9
0
Order By: Relevance
“…The meta-analysis and meta-regression used 88 observations from 26 different studies [5], [9], [12], [14], [16], [19][40]. Only 1 study estimated RR using hazard ratios [37] and all other studies used SMRs.…”
Section: Resultsmentioning
confidence: 99%
“…The meta-analysis and meta-regression used 88 observations from 26 different studies [5], [9], [12], [14], [16], [19][40]. Only 1 study estimated RR using hazard ratios [37] and all other studies used SMRs.…”
Section: Resultsmentioning
confidence: 99%
“…A UK study linked cause of death data to a register of those with diabetes and found that those with type‐1 diabetes only accounted for 18 (5%) of all deaths within the study; because of this they did not undertake separate analysis for cause of death among those with this form of diabetes 38. Other studies were characterised by their inclusion of numbers of concurrent type‐1 diabetes and cancer too small to elicit statistically viable results 39–42…”
Section: Resultsmentioning
confidence: 99%
“…We used a χ 2 test for trend to compare differences in the proportion of amputations by renal disease status (12). We used an α of 0.05 and 95% CI in the analysis.…”
Section: Methodsmentioning
confidence: 99%